2017
DOI: 10.25077/jka.v6i1.658
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Lama Terapi Antipsikotik dengan Kadar SGOT dan SGPT pada Pasien Skizofrenia di RSJ Prof. H.B Sa’anin, Padang Tahun 2013

Abstract: Beberapa antipsikotik, diantaranya klorpromazin, haloperidol, dan risperidon, telah diselidiki dapat menyebabkan drugs-induced liver injury, berupa kolestasis dan kerusakan hepatoselular. Pemeriksaan SGOT/AST dan SGPT/ALT digunakan untuk skrining kerusakan hati. Tujuan penelitian ini adalah untuk mengetahui hubungan lama terapi antipsikotik dengan kadar SGOT dan SGPT. Telah dilakukan penelitian secara potong-lintang terhadap pasien skizofrenia rawat inap dengan terapi kombinasi klorpromazin, haloperidol, dan r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
3
2
0
1
Order By: Relevance
“…There was no significant correlation between the duration of antipsychotic drug administration (1-6 months or more than 6 months) and transaminitis, which comes in line with Cahyaningtyas et al's finding that there was no significant association between short-term (≤ 6 months) and long-term (> 6 months) antipsychotic therapy and AST and ALT levels (Cahyaningtyas et al, 2017;Indira et al, 2017). Furthermore, our results support Atasoy et al's findings in absence of a statistically significant difference in the frequency of asymptomatic high liver enzyme in patients who received AD for shorter (< six months) or longer duration beyond six months (Atasoy et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…There was no significant correlation between the duration of antipsychotic drug administration (1-6 months or more than 6 months) and transaminitis, which comes in line with Cahyaningtyas et al's finding that there was no significant association between short-term (≤ 6 months) and long-term (> 6 months) antipsychotic therapy and AST and ALT levels (Cahyaningtyas et al, 2017;Indira et al, 2017). Furthermore, our results support Atasoy et al's findings in absence of a statistically significant difference in the frequency of asymptomatic high liver enzyme in patients who received AD for shorter (< six months) or longer duration beyond six months (Atasoy et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…Certain psychiatric disorders need long-term drug therapy, and the long-term use of antipsychotic drugs (AD) is correlated with a high risk of drug side effects, particularly DILI. Although there have been some studies that have investigated the association between the use of AD and impaired liver function, as well as the duration of drug use for these disorders, there is still a lot of inconsistency in the data (Cahyaningtyas et al , 2017; Yulianty et al , 2017; Anjelisa and Ruhi, 2018). Our study aimed to evaluate the impact of AD on serum transaminases in patients with psychiatric disorders, particularly the elevation of AST and ALT levels.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The data showed that the antipsychotic therapy duration 1-6 months and >6 months did not have a significant relationship with AST and ALT levels. This is consistent with Cahyaningtyas et al 13 which stated that there was no significant relationship between the duration of short-term (≤ 6 months) and long-term (> 6 months) combination of antipsychotic therapy with AST and ALT levels. 18 .…”
Section: Discussionsupporting
confidence: 91%
“…12 However, the results of this study are different from the other study stated that the levels of AST and ALT had no significant relationship with the duration of short and long-term antipsychotic therapy. 13 Schizophrenia is included in the top 10 mental disorders that require long-term pharmacotherapy. Long-term use of antipsychotics increases the risk of drug side effects, especially DILI, but this is not routinely monitored and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan obat dalam jangka panjang dapat menyebabkan kerusakan fungsi ginjal dan memperberat kerja ginjal sehingga menyebabkan ginjal tidak lagi berfungsi dengan baik. Antipsikotik adalah obat medis yang digunakan untuk mengobati gangguan mental, obat yang dikonsumsi pasien gangguan jiwa dapat menyebabkan toksisitas Cahyaningtyas et al (2013). Setelah dilakukan observasi di Rumah Sakit Jiwa Mutiara Sukma Provinsi NTB, diperoleh data sebanyak 285 orang dengan gangguan jiwa yang diperiksa kadar kreatininnya dari bulan Januari sampai dengan oktober tahun 2020.…”
unclassified